Quantitative high-resolution computed tomography fibrosis score: performance characteristics in idiopathic pulmonary fibrosis. Issue 3 (17th September 2018) - Humphries, Stephen M.; Swigris, Jeffrey J.; Brown, Kevin K.; Strand, Matthew; Gong, Qi; Sundy, John S.; Raghu, Ganesh; Schwarz, Marvin I.; Flaherty, Kevin R.; Sood, Rohit; O'Riordan, Thomas G.; Lynch, David A.
We evaluated performance characteristics and estimated the minimal clinically important difference (MCID) of data-driven texture analysis (DTA), a high-resolution computed tomography (HRCT)-derived measurement of lung fibrosis, in subjects with idiopathic pulmonary fibrosis (IPF). The study population included 141 subjects with IPF from two interventional clinical trials who had both baseline and nominal 54- or 60-week follow-up HRCT. DTA scores were computed and compared with forced vital capacity (FVC), diffusing capacity of the lung for carbon monoxide, distance covered during a 6-min walk test and St George's Respiratory Questionnaire scores to assess the method's reliability, validity and responsiveness. Anchor- and distribution-based methods were used to estimate its MCID. DTA had acceptable reliability in subjects appearing stable according to anchor variables at follow-up. Correlations between the DTA score and other clinical measurements at baseline were moderate to weak and in the hypothesised directions. Acceptable responsiveness was demonstrated by moderate to weak correlations (in the directions hypothesised) between changes in the DTA score and changes in other parameters. Using FVC as an anchor, MCID was estimated to be 3.4%. Quantification of lung fibrosis extent on HRCT using DTA is reliable, valid and responsive, and an increase of ∼3.4% represents a clinically important change. In subjects with IPF, quantification of lung fibrosis extent on HRCT using data-driven texture analysis shows acceptable performance characteristics and minimal clinically important difference in the range of 3.4–6.4% http://ow.ly/fFNc30lfAGh